Effects of Sanctions on EU – Russia Trade: A Gravity Model Approach - Garayev, Halmyrat (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This thesis studies trade relations between the European Union and the Russian Federation. The main objective is to see how international sanctions have affected bilateral trade volume between the Russia and the EU. Data for Russia and 28 European Union countries is used. The augmented gravity model with a panel data methodology is used. The main results suggest that distance between the countries has no effect on trade, another insignificant variable is the Linder variable that was manually calculated by the authors. Variables like GDP of EU member states and the GDP of Russia were significant and have a positive effect on trade. Variables representing common border and the exchange rates were significant and have a positive effect on trade. On the other hand, variables representing common history and sanctions have a negative impact on trade. As expected research found that sanctions have a negative impact on trade and should be avoided if possible. Keywords: International trade, Sanctions, Gravity model of trade.

ÖZ: Bu tez Avrupa Birliği ve Rusya Federasyonu arasındaki ticari ilişkileri incelemektedir. Esas amaç, uluslararası yaptırımların Rusya ve AB arasındaki ikili ticaret hacmini nasıl etkilediğini görmektir. Rusya ve 28 Avrupa Birliği ülkesi verileri kullanılır. Panel veri metodolojisi ile gelistirilmiş gravite modeli kullanılmıştır. Başlıca sonuçlar, ülkeler arasındaki mesafenin ticaret üzerinde hiçbir etkisinin olmadığını, başka bir önemsiz değişken ise yazarlar tarafından manuel olarak hesaplanan Linder değişkenidir. AB üyesi ülkelerin GSYH'sı ve Rusya'nın GSYH'sı gibi değişkenler önemliydi ve ticaret üzerinde olumlu bir etkiye sahipti. Ortak sınırı ve döviz kurlarını temsil eden değişkenler önemliydi ve ticaret üzerinde olumlu bir etkiye sahipti. Öte yandan, ortak tarih ve yaptırımları temsil eden değişkenlerin ticaret üzerinde olumsuz bir etkisi vardır. Beklendiği üzere, yaptırımların ticaret üzerinde olumsuz bir etkisi olduğu ve mümkünse önlenmelidir. Anahtar Kelimeler: Uluslararası ticaret, Yaptırımlar, Ticaretin Yerçekimi modeli.
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2019. Supervisor: Assoc. Prof. Dr. Çağay Coşkuner.
Keywords: Economics; International economic relations--Economic sanctions--European Union--Russia; Sanctions, Economic; International trade; Sanctions; Gravity model of trade